Processing and characterization of natural Bentonite from Aceh, Indonesia as filler of Poly-Caprolactone/Poly-Lactic Acid/Chitosan, (PCL/PLA/Chitosan) nanocomposites. Issue 1 (April 2020) - Ridwan,; Wirjosentono, B; Tamrin, T; Rihayat, T; Nurhanifa,
Abstract: The formation of composite from polymer mixture PCL / PLA / Chitosan bentonite was carried out through the melt intercalation method using an extruder at 180 °C with a holding time of 20 minutes. Bentonite is obtained from Kab. North Aceh which has been modified with CTAB surfactant. The sample formulations used were single PCL and PCL polymers each given 3, 5 and 8 % chitosan fillers. A mixture of PCL / PLA (50: 50) was given 3, 5 and 8 % chitosan / bentonite fillers. The sample is a white plastic rod (bone) material which is tested for its nature through several types of characterization. Modified bentonite and chitosan have an effect on increasing the mechanical and thermal properties of PCL, PLA and mixture polymers both based on the results of tensile test, TGA test (thermal) and bacterial test. PCL / PLA 50:50 with the addition of 8 % bentonite-chitosan filler is the most perfect composition which provides the best test value.